Is the modernisation of postgraduate medical training in the Netherlands successful? Views of the NVMO Special Interest Group on Postgraduate Medical Education. (February 2014) - Scheele, Fedde; Van Luijk, Scheltus; Mulder, Hanneke; Baane, Coby; Rooyen, Corry Den; De Hoog, Matthijs; Fokkema, Joanne; Heineman, Erik; Sluiter, Henk
<x xml:space="preserve">Abstract</x> Background: Worldwide, the modernisation of medical education is leading to the design and implementation of new postgraduate curricula. In this article, the Special Interest Group for postgraduate medical education of the Netherlands Association for Medical Education (NVMO) reports on the experiences in the Netherlands. Aim: To provide insight into the shift in the aims of postgraduate training, as well as into the diffusion of distinct curricular activities, introduced during the process of modernisation. Methods: Based on three levels of training described by Frenk et al., the process of modernisation in the Netherlands is reviewed in a narrative way, using the expert views of the NVMO-SIG on PGME as a source of information. Results: Educational science has effectively been incorporated and has until now mainly been applied on the level of informative learning to create 'medical expertise'. Implementing change on the level of formative learning for 'professional performance' has until now been a slow and arduous process, but the concept of reflection on practice has been firmly embraced. The training on the level of transformative learning is still in its early stages. Conclusion and recommendations: The discussion about the aims of modern medical education could benefit from a more structured and transdisciplinary approach. Research is warranted on the interface between health care provision and those sciences that specialise in generic professional skills and in the societal context. Training professionals and educating 'enlightened change agents' for transformation in health care requires more governance and support from academic leaders with a broader perspective on the future of health care.